Perancangan Aplikasi Prediksi Produksi Roti Menggunakan Metode Trend Moment - Sutriadi Sutriadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The monthly bread production data used by Mawar Bakery as a reference for production every day only uses uncertain manual estimates or only guesses and Mawar Bakery And Cake Shop also has not utilized or maximized computer technology. So that the production process often experiences a high rate of returns and often experiences shortages in certain months. In this condition, the company will experience losses due to high returns and the company may lose customers because it often experiences shortages in producing bread. Because the appropriate and timely bread production factors play a very important role in supporting the smooth production process at Mawar Bakery And Cake Shop. One method that can be used to solve this problem is the moment trend method. The trend method is an analytical method aimed at making predictions or predictions in the future. With the application of the prediction of the amount of bread production can reduce the rate of returns and the amount of raw material usage so as to reduce the amount of production costs and can produce healthy products.